The global spread of jellyfish hazards mirrors the pace of human imprint in the marine environment. - Lee, Sun-Hee; Tseng, Li-Chun; Yoon, Yang Ho; Ramírez-Romero, Eduardo; Hwang, Jiang-Shiou; Molinero, Juan Carlos (Elsevier, 2022)
The rising demand of ecosystem services, due to the increasing human population in coastal areas, and the subsequent need to secure healthy and sustainable seas constitute a major challenge for marine ecosystems management. In addition, global anthropogenic changes have transformed the marine realm, thereby challenging ecosystem health and the services necessary for human welfare. These changes have opened ecological space for opportunistic organisms, such as jellyfish, resulting in ecosystem-wide and economic implications that threaten marine ecosystem services. Here, we used a comprehensive dataset of jellyfish hazards over the period 1960–2019 to track their dynamics and implications for human welfare. Our results revealed that their large-scale patterns have been mainly enhanced in human-perturbed Large Marine Ecosystems, although the contribution of jellyfish Class to hazard type changed across ocean regions. The long-term variability of these events suggests that their temporal patterns mirror the pace of ocean warming and ocean health degradation nurtured by global anthropogenic changes in recent decades. These results warn of the wide socioecological risks of jellyfish hazards, and their implications advocate for transboundary, regional cooperation to develop effective ecosystem-based management actions. Failure to integrate jellyfish into ocean surveys will compromise coastal ecosystem services governance.
Keywords: Cambios climáticos - Efectos del hombre; Medusas - Distribución geográfica; Global anthropogenic changes; Marine ecosystem health; Marine biogeography; Ecosystem indicators; Gelatinous carnivore zooplankton